Pengukuran Dan Pemetaan Fotogrametris Menggunakan Unmaned Aerial Vehicle (UAV) Di Kota Samarinda Kelurahan Sungai Pinang Dalam - Wahyu Adiwinata; Muhammad Taufiq Sumadi; Fendy Yulianto (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
Soil plays an important role for all living things, where soil is a source of livelihood. It acts as a planting medium, a water reservoir, and a place for us to do activities. All of these activities are carried out on the land (Natasha Hutabarat et al., n.d.). In the community itself, land ownership is always a problem that is often encountered, whether it is the problem of unfixed land boundaries, land tenure, and land grabbing. The National Land Agency (BPN) as the institution that organizes land registration has a Complete Systematic Land Registration (PTSL) program that makes it easier for the community to register land so as to avoid land conflicts. In order to accelerate land registration, PTSL in Samarinda City this time uses media or tools to take measurements using the photogrammetric method, namely the Unmanned Aerial Vehicle (UAV) to obtain aerial images or the latest images. In its implementation, the community is asked to install boundary signs that have been delivered or socialized by BPN employees. So that the boundaries of the land plot can be seen from the UAV and visible from aerial images